Sorption characteristic of starch-based film - Basha, Roseliza Kadir; Leong, K. Y.; Othman, S. H.; Talib, R. A.; Naim, M. N.; Hasnan, N. Z. N.; Azmi, N. S. (Rynnye Lyan Resources, 2021)
Moisture sorption characteristic is important in determining the stability of bio-based plastic during packaging and storage condition. This study was carried out to investigate the moisture sorption characteristic of starch-based film. Moisture sorption test was conducted at different temperatures (5, 30 and 50°C) and relative humidity (23-75%). The experimental data was fitted using several models. Based on the Peleg model, the maximum rate of absorption and absorption capacity occurred at higher relative humidity. Guggenheim Anderson de Boer (GAB) model was the most suitable model to fit the experimental isotherm data and it is useful to predict the water sorption properties of the film which relate to different relative humidity conditions. In addition, the shelf life of film was reduced when placed under lower temperature due to the higher sorption capacity of moisture. The sorption properties of the starch-based film are important and worth investigation as it will be useful for the final application in food packaging due to its dependency on this behaviour.